PERENCANAAN KURIKULUM PENDIDIKAN ISLAM BERPOLA KURIKULUM MERDEKA DI SMK MUHAMMADIYAH KOTA BOGOR - Lukman Anwar; Endin Mujahidin; Syamsul Rizal Mz (Al-Mubin, 2023)
Curriculum planning is a part that determines whether educational institutions are good or not that will demonstrate the application of this curriculum in the learning process, the ultimate goal of which is to produce quality graduates as well. Therefore, every educational institution needs to have a very mature curriculum development plan to be implemented in the learning process. Islamic Education Curriculum is a learning experience. All learning activities that take place in educational institutions are part of the curriculum, both outside and inside the classroom. School is a miniature society. If the school is good, then society is too. In developing the curriculum, all parties involved in the preparation of curriculum planning need to work well together. Planning a curriculum requires careful preparation and strategy, because it is necessary to consider various aspects of the uniqueness of the curriculum that can be a differentiator from other schools. SMK Muhammadiyah Bogor City applies two curriculum models, namely the Holistic-Integrative Al-Islamic Education Curriculum, Kemuhammadiyahan and Arabic Language (ISMUBA) with the Independent Curriculum Pattern. The two models are combined or integrated into subjects so that according to expectations, the pedagogic component must work together in the form of careful planning and full readiness to achieve it